ANALISA PENGENDALIAN PROSES PRODUKSI SNACK MENGGUNAKAN METODE STATISTICAL PROCESS CONTROL (SPC) - Sidartawan, Robertus (ROTOR, 2014)
Today the growth of home industries increase rapidly indeed it is very competitive. One of the strategies to gain competitive advantage is to continuously improve the quality of its products. This conditions have to be supported by the implementation of a quality control on the process in order to later be able to produce a product that has high competitiveness. The purpose of this study is to analyze the production process of snacks at home industry whether they are already under statistical control or not and analyze whether the production process meets the specified design or not. The data are used in this study are both secondary and primary data. Primary data was obtained through direct observation and interviews, while the secondary data obtained from the internet, literature, and journals. Here, we use Statistical Process Control as the analytical tool by making X and R control charts and process capability analysis. The results showed that the control of the production process snacks still not reliable production process. This is an indication that the process is in out of control or it is still experiencing irregularities. Process capability ratio, indicating that the process is said to be worth (not capable) and it must be improved. Process capability index, indicating that the accuracy of the process is less, which means that the process can still be improved.Â Keywords: Statistical Process Control, Control Chart, Process Capability Â Â